2014
DOI: 10.1007/s00429-014-0788-7
|View full text |Cite
|
Sign up to set email alerts
|

Galanin receptor 2-neuropeptide Y Y1 receptor interactions in the amygdala lead to increased anxiolytic actions

Abstract: Galanin (GAL) and neuropeptide Y (NPY) are neuropeptides involved in behaviors associated with anxiety. Both neuropeptides interact in several central functions. However, the potential behavioral and cellular interactions between them in anxiety are unknown. GAL was found to act through GAL receptor 2 (GALR2) to enhance NPYY1 receptor (NPYY1R)-mediated anxiolytic behaviors in rats. Using receptor autoradiography, c-Fos expression and in situ proximity ligation assay, the medial paracapsular intercalated nuclei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 39 publications
9
44
0
Order By: Relevance
“…In the open field, in agreement with other authors ( Narvaez et al, 2014 ) the dose of 3 nmol of GAL did not affect the time spent in and number of entries into the central square in the open field ( Figure 2C and D ). In view of the fact that GAL(1–15) at 3 nmol significantly decreased the time ( t = 2.318, p < 0.05, df = 13) and number ( t = 3.379, p < 0.01, df = 16) of entries in the open field, our results indicate than only GAL(1–15) and not GAL modifies the anxiety parameters in the present model.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In the open field, in agreement with other authors ( Narvaez et al, 2014 ) the dose of 3 nmol of GAL did not affect the time spent in and number of entries into the central square in the open field ( Figure 2C and D ). In view of the fact that GAL(1–15) at 3 nmol significantly decreased the time ( t = 2.318, p < 0.05, df = 13) and number ( t = 3.379, p < 0.01, df = 16) of entries in the open field, our results indicate than only GAL(1–15) and not GAL modifies the anxiety parameters in the present model.…”
Section: Resultssupporting
confidence: 93%
“…After each trial, all surfaces were cleaned with a paper towel and 70% ethanol solution. For the open-field (100 x 100 x 50cm), total time spent in and entries into the inner square were recorded ( Grivas et al, 2013 ; Narvaez et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain neuropeptide systems participate in the behaviors associated with anxiety. It has been shown that long-term dysregulation of these systems contributes to the development of anxiety disorders, including PTSD [9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that Galanin (Gal) and its three general receptor subtypes known as GalR1, GalR2 and Gal R3, play a significant role in anxiety, depression, and stress-like behaviors through modulation of neuroendocrine, serotonergic and noradrenergic systems [1013]There are also reports suggesting that Gal has antidepressant effects[14] [15]…”
Section: Introductionmentioning
confidence: 99%